2005
DOI: 10.1524/ract.2005.93.12.781
|View full text |Cite
|
Sign up to set email alerts
|

Determination of uranium concentration and burn-up of irradiated reactor fuel in contaminated areas in Belarus using uranium isotopic ratios in soil samples

Abstract: SummaryAn analytical method is described for the estimation of uranium concentrations, of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…253,263 Soil solutions have been analysed in largely different studies for (i) As species using hyphenated techniques, 264 (ii) Ge/Si ratios to assess the relative contributions of weathering and biogenic silica cycling 261 and (iii) total and EDTA extractable metal distributions in the colloidal fraction of contaminated soil employing sedimentation field-flow fractionation coupled online to HR-ICP-MS. 262 There has also been considerable interest in the determination of U and Pu in soil samples for both concentrations and isotope ratios. [265][266][267][268][269][270][271] As such, mainly the 236 U isotope was used to trace spent U from nuclear fallout related to the accident at the Chernobyl nuclear power plant in 1986. [265][266][267][268][269] Isotopic analysis of U and Pu was also successfully applied to estimate burn-up of spent U in contaminated environmental samples 270 as well as the identification of depleted U in soil samples collected in Kosovo.…”
Section: Soils Sediments Particulate Matter and Aerosolsmentioning
confidence: 99%
See 2 more Smart Citations
“…253,263 Soil solutions have been analysed in largely different studies for (i) As species using hyphenated techniques, 264 (ii) Ge/Si ratios to assess the relative contributions of weathering and biogenic silica cycling 261 and (iii) total and EDTA extractable metal distributions in the colloidal fraction of contaminated soil employing sedimentation field-flow fractionation coupled online to HR-ICP-MS. 262 There has also been considerable interest in the determination of U and Pu in soil samples for both concentrations and isotope ratios. [265][266][267][268][269][270][271] As such, mainly the 236 U isotope was used to trace spent U from nuclear fallout related to the accident at the Chernobyl nuclear power plant in 1986. [265][266][267][268][269] Isotopic analysis of U and Pu was also successfully applied to estimate burn-up of spent U in contaminated environmental samples 270 as well as the identification of depleted U in soil samples collected in Kosovo.…”
Section: Soils Sediments Particulate Matter and Aerosolsmentioning
confidence: 99%
“…[265][266][267][268][269][270][271] As such, mainly the 236 U isotope was used to trace spent U from nuclear fallout related to the accident at the Chernobyl nuclear power plant in 1986. [265][266][267][268][269] Isotopic analysis of U and Pu was also successfully applied to estimate burn-up of spent U in contaminated environmental samples 270 as well as the identification of depleted U in soil samples collected in Kosovo. 271 Plutonium isotopes and other radionuclides were determined in soil and sediment reference materials, 272,273 radioactive ''hot'' particles and depth profiles of Chernobyl fallout-contaminated soils, [273][274][275] as well as soil profiles and sediment cores from other regions of the globe.…”
Section: Soils Sediments Particulate Matter and Aerosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…A research group at Umea˚University in Sweden have developed a means of generating species-specific standards on demand. 25 Permeation tube standards, i.e., sealed plastic tubes containing liquid standards held at constant temperature and in equilibrium with the resultant headspace gas, were prepared with the following species specific enriched isotopes: 202 Hg 0 , 201 HgCl 2 , (CH 3 ) 2 198 Hg and CH 3 201 HgCl. By passing a sweep gas over the tubes, these gaseous standards are released at a constant rate by diffusion through the walls of the permeation tube.…”
Section: Isotopic Analysismentioning
confidence: 99%
“…234 U and 230 Th were determined by FIA-ICP-MS in an application to look at the uranium series disequilibrium in marine sediments. 199 Two studies have looked at low levels of U in soil samples collected in the vicinity of the Chernobyl nuclear power plant, 200,201 whilst the sample clean-up required for such studies has also been investigated. 202 The determination of 99 Tc in both soils and radioactive wastes has been achieved using anion exchange chromatography coupled to ICP-MS. 203 In another application, high precision measurement of Hg isotopic ratios in sediments was achieved using cold vapour generation multicollector ICP-MS. 204 This study confirmed that the long term precision and accuracy possible using this technique was sufficient to detect even small differences in Hg isotopic ratios in sediment samples.…”
Section: Mass Spectrometrymentioning
confidence: 99%